IMPLEMENTASI PROGRAM PEMBERDAYAAN EKONOMI RAKYAT MELALUI PROGRAM MAMANGUN TUNTANG MAHAGA LEWU (PM2L) (Studi Kasus di Dua Desa Tertinggal di Kalimantan Tengah) - Karlina Batik; Agus Suman (Jurnal Ekonomi Pembangunan, 2013)
This study aims to determine the implementation of the program of economic empowerment of the people through the program mamangun Tuntang mahaga Lewu (PM2L). Writing method used is qualitative. This method was chosen because it examines the phenomenon of something in more depth, and more able to understand the phenomenon that until now has not been known. Through this study were obtained in the implementation of key information that PM2L are several stages to go through the stage of coordination, socialization, implementation of the action, coaching, monitoring and evaluation. In general, the stages through which it has not been optimal program implementation in practice, especially in terms of stages of development.